KHASHAA’ISH AL-AHKAM DALAM KELUARGA ISLAM (Analisis terhadap Penetapan Status dan Tanggung Jawab Orang Tua Kepada Anak) - Suharti (Prodi Hukum Keluarga Islam IAI Uluwiyah Mojokerto, 2026)
This studi examines Khashaa’ish al-Ahkām (characteristics of Islamic law) as the foundation for determining the status and responsibilities of parents toward children in Islamic family law. The method employed is a literature study with a normative qualitative approach, through the analysis of various sources such as the Al-Qur'an, hadith, classical and contemporary fiqh books, and others. The research findings reveal that parental responsibilities include providing sustenance, spiritual, moral, and intellectual education, with the aim of shaping children who are faithful, pious, and possess virtuous character. Islamic law offers flexible and dynamic guidance to fulfill these responsibilities harmoniously between social progress and justice in the family, ensuring comprehensive protection of rights and obligations.